1976
DOI: 10.1128/jb.128.1.202-211.1976
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of histidinol phosphate aminotransferase synthesis by tryptophan in Bacillus subtilis

Abstract: The effect of tryptophan on the synthesis of histidinol phosphate aminotransferase and prephenate dehydrogenase has been examined. The genes specifying two enzymes for tryptophan biosynthesis (anthranilate synthase and tryptophan synthase-B) were found to be derepressed in a temporal sequence according to their chromosomal location. The genes for histidinol phosphate aminotransferase and prephenate dehydrogenase were derepressed simultaneously approximately 8 min after tryptophan synthase-B. When excess trypto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Beside the induction of these genes, also tyrA, encoding the prephenate dehydrogenase, was induced. In B. subtilis, a co-regulation of the trp genes with hisC and tyrA has been reported [64]. Expression of the genes involved in tryptophan biosynthesis is regulated in B. subtilis in response to the tryptophan availability by the trp RNA-binding attenuation protein (TRAP) [65].…”
Section: Nitrogen Starvationmentioning
confidence: 99%
“…Beside the induction of these genes, also tyrA, encoding the prephenate dehydrogenase, was induced. In B. subtilis, a co-regulation of the trp genes with hisC and tyrA has been reported [64]. Expression of the genes involved in tryptophan biosynthesis is regulated in B. subtilis in response to the tryptophan availability by the trp RNA-binding attenuation protein (TRAP) [65].…”
Section: Nitrogen Starvationmentioning
confidence: 99%
“…In these experiments the biosynthetic reaction was measured, with the exception of His-P because the substrate 3-(imidazol-4-yl)-2-oxopropyl phosphate was not accessible (Table 2). HisC is the only aminotransferase active in l-His formation in C. glutamicum since a hisC-deletion mutant of C. glutamicum requires l-His for growth (data not shown), similar to other bacteria such as E. coli or Bacillus subtilis (Garrick-Silversmith & Hartman, 1970;Weigent & Nester, 1976). The activity with phenylpyruvate (O-Phe) and the other aromatic oxoacids does not contribute to aromatic amino-acid synthesis in C. glutamicum in vivo (Marienhagen et al, 2005), possibly owing to the low affinity of HisC (see below).…”
Section: General Characteristics Of Hiscmentioning
confidence: 62%
“…3). In the amino-acid sequences of Z. mobilis and B. subtilis HisC a phenylalanine residue is located at this position and Sivaraman et al 2001 contribute to the observed broader substrate specificity for aromatic amino acids in these two enzymes (Gu et al, 1995;Weigent & Nester, 1976). Amino-acid replacement by sitedirected mutagenesis at this position (Tyr123Phe) led to only moderate changes in kinetic constants with the natural substrate and the reactions with aromatic substrates were influenced even less (Table 3).…”
Section: Structural Basis For Substrate Specificity In Histidinol-phomentioning
confidence: 99%